Ethnobotany of the Carob Tree (Ceratonia siliqua): Nutritional, Medicinal, and Ecological Significance - SABOUR ALAOUI SANAA (Natural Resources for Human Health, 2026)
The carob tree (Ceratonia siliqua), a leguminous species native to the Mediterranean basin, holds a prominent place in regional ethnobotany due to its multifaceted uses in traditional diets, natural medicine, and agroecological systems. Belonging to the Fabaceae family, this fruit-bearing tree is appreciated for its nutritional richness: its pulp is high in natural sugars, the seeds contain valuable fats, and the pods are a source of essential minerals such as potassium, calcium, and phosphorus. Moreover, its leaves and pods are rich in polyphenols and antioxidants. From an ecological standpoint, the carob tree demonstrates exceptional resilience to water scarcity, making it a strategic species for reforestation and land restoration in arid and degraded environments. Economically, it has significant value, as its derivatives are employed in the food, pharmaceutical, and cosmetic industries. This review provides an overview of the chemical composition and bioactive properties of Ceratonia siliqua, while emphasizing its ethnobotanical relevance and its contributions to human health and sustainable development.